Evaluación del riesgo ergonómico por carga física en los estibadores portuarios del puerto Masusa - Iquitos. Loreto - Perú. 2022 - Da Silva Cahuaza, Yanely Salely (2023)
In the river port of Masusa, located in the district of Punchana, a study was carried out to measure whether stevedores presented ergonomic risks as a result of physical effort when loading and unloading cargo, where it was determined that One of the main problems regarding the stevedore job position in the port of masusa is the lack of sufficient spaces and disorder in the places used to move with the loads, each stevedore has to handle loads that exceed 50 kg in weight, considered by themselves as loads heavy that threaten their physical health. Working in forced postures, such as bending over, bending over, lifting loads from the floor to load or unload merchandise Repetitively, it is considered routine work, which when carried out for long periods of time can have negative consequences for health, as a consequence of this work there have been health problems, a feeling of fatigue and tiredness during and after work days, these problems manifest as discomfort and pain in part of the back, shoulders and neck, these physical discomforts are the product of the very high level of risk that they have when adopting inappropriate postures when carrying out stowage tasks, so that the working conditions and the physical health of the stevedores can be seen to improve, immediate action is needed directly and indirectly involved in the fluvial port.